Pericoronary adipose tissue attenuation, low-attenuation plaque burden and 5-year risk of myocardial infarction. (14th October 2021) - Tzolos, E; Williams, M C; McElhinney, P; Lin, A; Grodecki, K; Guadalupe, F T; Cadet, S; Berman, D S; Slomka, P J; Dweck, M R; Newby, D E; Dey, D E
Abstract: Introduction: Pericoronary adipose tissue (PCAT) attenuation has emerged as a surrogate marker of pericoronary inflammation. To date, no studies have compared the impact of pericoronary adipose tissue (PCAT) attenuation and quantitative plaque burden on cardiac outcomes. Purpose: We aimed to establish the relative merits of these approaches to risk prediction and hypothesised that the combination of PCAT attenuation and quantitative plaque burden measures could provide additive and improved prediction of myocardial infarction in patients with stable chest pain. Methods: In a post-hoc analysis of a randomized controlled trial, we investigated the association between the future risk of fatal or non-fatal myocardial infarction and PCAT attenuation measured from CT coronary angiography using multivariable Cox regression models including plaque burden, obstructive coronary disease and cardiac risk score (incorporating age, sex, diabetes, smoking, hypertension, hyperlipidaemia and family history of cardiovascular disease). Results: In 1697 evaluable participants (mean age 58±10 years), there were 37 myocardial infarctions after a median follow-up of 4.7 [interquartile interval, 4.0–5.7] years. Median low-attenuation plaque burden was 4.20 [0–6.86] % and mean PCAT −76±8 Hounsfield units (HU). PCAT attenuation of the right coronary artery (RCA) was predictive of myocardial infarction (hazard ratio [HR] 1.55, 95% CI 1.08–2.22; p=0.017, per 1 standard deviation increment) with an optimum threshold of −70.5 HU [Hazards ratio (HR) 2.45, 95% CI 1.2–4.9; p=0.01]. Univariable analysis also identified the burden of non-calcified, low-attenuation and calcified plaque as well as Agatston coronary calcium score, presence of obstructive coronary artery disease and cardiovascular risk score were predictors of myocardial infarction (Figure 1). In multivariable analysis, only the low-attenuation plaque burden (HR 1.80, 95% CI 1.16 to 2.81, p=0.011, per doubling) and PCAT-RCA (HR 1.47 95%1.02 to 2.13, p=0.040, per standard deviation increment) remained predictors of myocardial infarction (Figure 1). In multivariable analysis, adding PCAT-RCA ≥-70.5 HU to low-attenuation plaque burden >4% (optimum threshold for future myocardial infarction; HR = 4.87, 95% CI 2.03–11.78; p<0.0001) led to improved prediction of future myocardial infarction (HR 11.7, 95% CI 3.3–40.9; p<0.0001); Figure 2. In ROC analysis, integration of PCAT-RCA attenuation and LAP burden, increased the prediction for myocardial infarction compared to LAP alone (ΔAUC=0.04; p=0.01). Conclusion: CT coronary angiography defined PCAT attenuation and low-attenuation plaque have marked and additive predictive value for the risk of fatal or non-fatal myocardial infarction. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The Chief Scientist Office of the Scottish Government Health and Social Care Directorates, British Heart Foundation, National Institute of Health/National Heart, Lung, and Blood Institute grant